Compresión de Audio Basada en Codificación Subbanda - Llanos, Aura Polo; Algarín, Carlos Robles; Fula, Jordan Guillot (KnE Engineering, 2018)
An eight channels subband audio codec is implemented for signals with 44.1 KHz and 16 bits per sample using Matlab. To achieve perfect reconstruction, a two channels QMF filter bank with cutoff frequency ω=π/2 is designed, based on an equiriple filter of 99 order. Seven stages of this bank are used to split the input into eight signals with sample rates from 2.76 to 11 KHz, which are coded from 1 to 16 bits depending on the band energy. To evaluate performance for three tracks in terms of similarity of input and output signals, a Mean Opinion Score (MOS) experiment with fifteen subjects was performed. The Euclidean Distance between spectrums was also measured. Results showed a fair similitude for two tracks and excellent for one. Compression factors above 96% were achieved. Keywords: subband coding, mean opinion score MOS, QMF filter banks, audio compression